2022
DOI: 10.1155/2022/5630487
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Mayinglong Musk Hemorrhoid Ointment on Wound Healing and Complications after Internal Hemorrhoid Ligation and External Hemorrhoidectomy

Abstract: Objective. To investigate the effect of Mayinglong Musk Hemorrhoids Ointment on wound healing and complications after internal hemorrhoid ligation and external hemorrhoidectomy. Methods. This is a retrospective study. A total of 100 patients with mixed hemorrhoids who were treated in our hospital from August 2019 to October 2020 were recruited and assigned to an operation group (n = 50, internal hemorrhoid ligation, and external hemorrhoidectomy) or a combined group (n = 50, use of Mayinglong Musk Hemorrhoid O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This is because after surgery, especially excisional haemorrhoidectomy, postoperative pain, which generally results from a spasm of the internal anal sphincter, causes many issues for patients [ 2 ]. For the treatment of postoperative pain in patients after haemorrhoidectomy, people often choose different methods, such as sitz baths [ 29 ], medications to reduce swelling [ 32 ] or topical anaesthesia [ 33 ]. Chemical sphincterotomy, which is always used for patients with anal fissures, can reduce spasms of the internal anal sphincter and relieve pain [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because after surgery, especially excisional haemorrhoidectomy, postoperative pain, which generally results from a spasm of the internal anal sphincter, causes many issues for patients [ 2 ]. For the treatment of postoperative pain in patients after haemorrhoidectomy, people often choose different methods, such as sitz baths [ 29 ], medications to reduce swelling [ 32 ] or topical anaesthesia [ 33 ]. Chemical sphincterotomy, which is always used for patients with anal fissures, can reduce spasms of the internal anal sphincter and relieve pain [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has the advantages of unclogging meridians and collaterals, invigorating blood flow and relieving pain. At present, the clinical research on acupuncture and moxibustion for postoperative pain of hemorrhoids is obviously insufficient, there is a small sample size and no uniform evaluation index, so this study uses meta analysis to evaluate the effect of acupuncture on postoperative pain complications of hemorrhoids compared with traditional chinese medicine [10] and western medicine. In order to provide a reference for the clinical study of acupuncture and moxibustion in the treatment of postoperative complications of anal intestinal diseases.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%